Lidar-based Studies of Aerosol Optical Properties Over Coastal Areas - Bringfried Pflug; Tymon Zielinski (Sensors, 2007)
Aerosol size distribution and concentration strongly depend on wind speed,direction, and measuring point location in the marine boundary layer over coastal areas.The marine aerosol particles which are found over the sea waves in high wind conditionsaffect visible and near infrared propagation for paths that pass very close to the surface aswell as the remote sensing measurements of the sea surface. These particles are producedby various air sea interactions. This paper presents the results of measurements taken atnumerous coastal stations between 1992 and 2006 using an FLS-12 lidar system togetherwith other supporting instrumentation. The investigations demonstrated that near-waterlayers in coastal areas differ significantly from those over open seas both in terms ofstructure and physical properties. Taking into consideration the above mentioned factors,aerosol concentrations and optical properties were determined in the marine boundary layeras a function of offshore distance and altitude at various coastal sites in two seasons. Thelidar results show that the remote sensing algorithms used currently in coastal areas needverification and are not fully reliable.